Headache and Chiari-I Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The clinical features and pathogenesis of headache associated with Chiari-I malformation and syringomyelia are reviewed from the Katholieke Universiteit Leuven, Belgium.